TERRITORIAL ORGANIZATION OF THE ECONOMY AND ITS INSTITUTIONAL SECURITY IN MODERN CONDITIONS - KHARCHENKO, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Optimization of institutional support contributes to the successful functioning of not only any region of Ukraine, but also the country as a whole and depends on many factors. The cumulative potential of each individual region is formed at the expense of its resource components, which, under the condition of effective management, could provide modernization processes, including developed interregional and international connections. Thus, in the modern realities of military actions and post-war activities, there is a need to rethink the policy of territorial organization of the economy through the prism of spatial priorities in the conditions of expanding object-subject relations. Therefore, it is necessary to ensure the systematicity of management influences, the mutual coordination of powers and their resource provision, as well as strengthening the responsibility of regional and local authorities. In the article authorial researches of features of influence of territorial organization of economy are carried out and her institutional providing, враховуючі modern calls, possibility of creation of new and strengthening of existent methodological contradictions. Spatial organization of economy is certain as a result and display of territorial division of labour, territorial processes as phenomena of differentiation of integration and concentration of managing subjects are investigational on different taxonomical levels. The forms of territorial organization of economies are distinguished and them taxonomical display. It is marked that placing of any sphere of activity can be examined as sectoral constituents of economic regions within the limits of one country or entire world. It is possible to district inter-branch complexes such method